Northwest History. Alaska. Floods & Flood Control. (1937)
New Floods Sweep Down Yukon River. New Floods Sweep Down Yukon River FAIRBANKS, Alaska, May 18. (/P)—Fresh floods in the JTukon river basin washed through Nenana and Fort Yukon today and drove residents from their homes and places of business. Several feet of water flowed through Fort Yukon, a trading post 150 miles northeast of here at the junction on the Yukon and Porcupine rivers. It has a few hundred permanent residents. 350, of which most are Indians. The residential district of Nenana, 50 miles southwest of here, lay deep in the overflow of the Tanana river which covered the lower part of the town with 14 feet of water at the crest. Water ran through the business section and railroad yards. Nenana's population is less than 1,000. Estimates of property damage were unavailable at either place. Radiophone reports from Fort Yukon and Nenana mentioned no fatalities. Nenana is the connecting line for steamers that go north on the Yukon and Alaska railroad south. Fort Yukon's population is 350, of which most are Indians. The settlement is one of Alaska's largest fur trading centers, with a transient population of natives, trappers, fishermen and miners. Sweeps Fort Water swept into Fort Yukon Saturday night as the Yukon river ice broke. The flood carried away one cabin, loose equipment and fences and sent most of the population to boats, higher ground or buildings of more than one story. The Nenana flood flollowed closely the one which spread through three-fourths of Fairbanks last week, as the ice-gorged Tanana and Chena rivers left their banks.